MENUMBUHKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA DINI: STUDI PENGEMBANGAN MEDIA PERMAINAN SNAKES AND LADDERS DI TK OXFORD PURI SCHOOL PPS MANYAR GRESIK - Nina Nuriyah Ma'arif; Fifi Mazroatul Ummah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
This article reports on a study of the research and development (R&D) model regarding the development of instructional media called snakes and ladders game to foster early childhood (4-5 years old) logical thinking skills conducted at Kindergarten Oxford Puri School PPS Manyar Gresik. Using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) promoted by Dick and Carry and descriptive quantitative analysis, the results of this study state that the game media